SUB-OCEAN: subsea dissolved methane measurements using an embedded laser spectrometer technology - Grilli, Roberto; Triest, Jack; Chappellaz, Jérôme; Calzas, Michel; Desbois, Thibault; Jansson, Pær; Guillerm, Christophe; Ferré, Benedicte; Lechevallier, Loïc; Ledoux, Victor; Romanini, Daniele (Environmental Science & Technology, 2018)
This document is the Accepted Manuscript version of a Published Work that appeared in final form in Environmental Science and Technology , copyright © American Chemical Society after peer review and technical editing by the publisher. To access the final edited and published work see https://doi.org/10.1021/acs.est.7b06171 . We present a novel instrument, the Sub-Ocean probe, allowing in situ and continuous measurements of dissolved methane in seawater. It relies on an optical feedback cavity enhanced absorption technique designed for trace gas measurements and coupled to a patent-pending sample extraction method. The considerable advantage of the instrument compared with existing ones lies in its fast response time of the order of 30 s, that makes this probe ideal for fast and continuous 3D-mapping of dissolved methane in water. It could work up to 40 MPa of external pressure and it provides a large dynamic range, from subnmol of CH 4 per liter of seawater to mmol L -1 . In this work, we present laboratory calibration of the instrument, intercomparison with standard method and field results on methane detection. The good agreement with the headspace equilibration technique followed by gas-chromatography analysis supports the utility and accuracy of the instrument. A continuous 620-m depth vertical profile in the Mediterranean Sea was obtained within only 10 min and it indicates background dissolved CH 4 values between 1 and 2 nmol L -1 below the pycnocline, similar to previous observations conducted in different ocean settings. It also reveals a methane maximum at around 6 m of depth that may reflect local production from bacterial transformation of dissolved organic matter.